A study of hotel workers' perception of the impact of tourism industry on their social life in Langkawi, Malaysia - Rosfazila Binti Hj. Abd. Rahman (International Islamic University Malaysia, 2005)
This study focuses mainly on hotel workers' perception of the impact of tourism industry on their social life in Langkawi, Malaysia. It assesses the hotel workers' perception of changes brought about by tourism in their social life and their reaction thereof. It also assesses the changing pattern of economy as well as the environment and their impact on the life of people in general and of hotel workers in particular. The present study focuses on the social impact of tourism on hotel workers. It opens new vistas of understanding the youth culture in the region. Social scientists neglected this aspect and most of the previous researches only concentrated on physical impacts of tourism (environmental, economy and lifestyle at large). By that the economic gains are more concerned than the social life of youths. In order to expose and highlight the issues involved in it, thus, this study concentrates on analyzing the social impact of tourism particularly on hotel workers of Langkawi, Malaysia. The present research studies the changes brought about by tourism and affected, to a great extent, the social life of hotel workers. It assesses hotel workers perception of the changes and the extent they affected their attitude, aspirations and way of life. It also tries to find out their reaction towards tourism and its positive and negative effects on the region. It further assesses how they adapt to these changes with particular reference to family relation and religion. The study adopts quantitative methodology and data is derived from both primary and secondary sources. Questionnaire is administered among hotel workers in Langkawi to find out their perception of the impact of tourism industry on their social life.